Quality and Energy Performance of Briquettes Derived from Non-Timber Forest Product Residues: A Case Study of Sugar Palm (Arenga pinnata) - Wulandari, Febriana Tri; Nikmatullah, Aluh; Latifah, Sitti; Hayati, Hayati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The utilization of non-wood biomass residues as alternative solid fuels is important for supporting low-carbon energy transitions and circular bioenergy development. This study evaluated the quality and energy performance of charcoal briquettes produced from vegetative residues of sugar palm (Arenga pinnata), specifically fronds, fruit stalks, and a mixture of both materials. A completely randomized design was applied, and the briquettes were assessed based on physical properties, proximate composition, combustion performance, and charcoal yield, with SNI 01-6235-2000 used as the primary quality benchmark. The results showed that all briquette types had very low moisture content (1.69–2.03%) and high calorific values (5,427–5,985 cal g⁻¹), meeting the SNI requirements for these parameters. Significant differences among plant parts were observed in ash content, volatile matter, and fixed carbon content (p < 0.05), indicating that raw material characteristics strongly influenced briquette quality. Briquettes produced from sugar palm fronds exhibited the highest fixed carbon content and calorific value, as well as the lowest burning rate, reflecting better thermal stability and longer combustion duration. Meanwhile, briquettes made from the mixture of fronds and fruit stalks showed the lowest ash content and the most balanced quality profile. Although some proximate parameters, particularly volatile matter and fixed carbon, did not fully meet the SNI limits, these limitations are process-dependent and may be improved through optimization of carbonization conditions. Overall, sugar palm vegetative residues represent a promising non-wood biomass resource for sustainable charcoal briquette production within a circular bioenergy framework.